The Role of AI and Automation in Revolutionizing the Modern Medical Environment: A Systematic Review - Asiri, Hanan Mofareh Ahmed; Al Muhmal, Mofareh Hassan Mohammed; Asiri, Sara Mofareh Ahmed; Jali, Asim Mohammed Ali; Assiri , Tahani Ahmed Mohammed; Al Murayh, Hussain Ali Saleh; Algamsh, Abdullah Hussain; abutaleb, Ohood Mohammed Yahya (Journal of Ecohumanism, 2024)
Background: The integration of Artificial Intelligence (AI) and automation in healthcare has emerged as a transformative force, reshaping the modern medical environment. These technologies promise to enhance operational efficiency, improve diagnostic accuracy, and optimize patient care. However, their adoption also raises ethical, technical, and operational challenges. Objective: This systematic review aims to explore the impact of AI and automation on the healthcare sector, focusing on their applications, benefits, challenges, and future potential. Methods: A systematic search was conducted across major databases, including PubMed, Scopus, and Web of Science, to identify peer-reviewed studies published between 2016 and 2024. Studies were selected based on their relevance to AI and automation in medical environments, using predefined inclusion and exclusion criteria. Data were extracted and analyzed to identify key themes. Results: The review identified significant advancements in AI-driven diagnostics, robotic-assisted surgeries, workflow automation, and predictive analytics. These technologies have demonstrated measurable improvements in clinical outcomes, operational efficiency, and cost reduction. However, challenges such as data privacy, ethical concerns, and integration issues persist. Conclusion: AI and automation are revolutionizing healthcare by streamlining processes, enhancing patient outcomes, and addressing resource limitations. Despite current challenges, their potential to transform the medical environment is undeniable. Further research and multidisciplinary collaboration are essential to overcome barriers and fully harness these technologies.